CLINICAL ANALYSIS OF REMAINING CORONAL TOOTH STRUCTURE IN RELATION WITH PREFABRICATED METAL POSTS IN MOLARS- A RETROSPECTIVE ANALYSIS - T, Keerthana; Ramesh, Sindhu; S, Deepak. (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Endodontically treated teeth, which have extensive structural defects due to caries, access cavity preparation requires post- and core management for retention purposes. The clinical decision is to decide whether an endodontically treated tooth requires a post and a crown, which poses a challenge to dental practitioners.Aim: The study aims at analysing remaining coronal tooth structure in relation to prefabricated metal posts in molars.Materials and Method: This retrospective clinical study evaluated the patients who received prefabricated metal posts in endodontically treated molars from the department of Conservative Dentistry and Endodontics in a dental college located in Chennai. A total of 373 patient’s records were evaluated from June 2019 to March 2020, and based on inclusion and exclusion criteria, selected data consisted of 219 patients who received prefabricated metal posts in endodontically treated molars. Inclusion criteria consisted of patients aged between 18 and 60 who received prefabricated metal posts in endodontically treated molars. Exclusion criteria consisted of patients who received FRC and cast post in endodontically treated teeth other than molars.Results: In this study, 219 patients (104 are females, 115 are males, with a mean age group of 30 years) were included. It is observed that there is a significant difference among the groups. Group B (coronal tooth structure, 2 to 4 mm) was highly noted in endodontically treated molars with prefabricated metal posts compared to other groups with a p value